A universal and enzyme-free immunoassay platform for biomarker detection based on gold nanoparticle enumeration with a dark-field microscope. Issue 22 (16th October 2017) - Wu, Xi; Li, Tian; Tao, Guangyu; Lin, Ruoyun; Pei, Xiaojing; Liu, Feng; Li, Na
Abstract : We develop a universal and enzyme-free magnetic bead-based sandwich-format immunoassay platform for biomarker detection by combining secondary antibody functionalized AuNPs and automatic AuNP counting. Abstract : Developing an enzyme-free, non-amplification strategy for biomarker detection with universality and easy implementation is of central importance in clinical diagnosis and therapeutic monitoring. Herein, we report for the first time a universal and enzyme-free magnetic bead-based sandwich-format immunoassay platform for biomarker detection by combining secondary antibody functionalized AuNPs and automatic AuNP counting readout. For the prostate specific antigen (PSA), the detection limit is found to be 1 ng mL −1, and the spike recoveries ( n = 3) with 10% fetal bovine serum are 113.5% for 2 ng mL −1 and 107.7% for 10 ng mL −1 . The assay also presents reasonable repeatability as indicated by the coefficient of variance of 13.1% with 5 measurements in 60 days. This strategy has been successfully applied to the determination of carcinoembryonic antigen (CEA) and alpha-fetoprotein (AFP), demonstrating the universality of this strategy. Our proposed non-amplification platform presents sensitivity comparable to that of the enzyme-linked immunosorbent assay (ELISA) with better repeatability; and more importantly, our method has better simplicity than most of the amplification-based methods, and thus is more suitable for routine analysis. The highlights of our work suggest that it is a promising method and would be potentially an alternative for ELISA in laboratories where routine analyses are intensively performed.